Defining the core components of Family Navigation for autism spectrum disorder. (February 2020) - Broder-Fingert, Sarabeth; Stadnick, Nicole A; Hickey, Emily; Goupil, Julia; Diaz Lindhart, Yaminette; Feinberg, Emily
This study aimed to define the core components of Family Navigation for autism spectrum disorder, a promising intervention to reduce disparities in care for this population. Teams from four trials of Family Navigation for autism spectrum disorder completed the Template for Intervention Description and Replication checklist to outline intervention components. Through intervention component analysis and qualitative synthesis, we identified 11 core components across three domains: Training and Supervision, Navigator Tools, and Navigator Activities. We discuss the importance of identifying these core components and implications for future research and practice.